Evaluation on reprogramed biological processes in transgenic maize varieties using transcriptomics and metabolomics - Wei Fu (Nature Portfolio, 2021)
Abstract Genetic engineering (GM) has great potential to improve maize productivity, but rises some concerns on unintended effects, and equivalent as their comparators. There are some limitations through targeted analysis to detect the UE in genetically modified organisms in many previous studies. We here reported a case-study on the effects of introducing herbicides and insect resistance (HIR) gene cassette on molecular profiling (transcripts and metabolites) in a popular maize variety Zhengdan958 (ZD958) in China. We found that introducing HIR gene cassette bring a limited numbers of differential abundant genes (DAGs) or differential abundant metabolites (DAMs) between transgenic events and non-transgenic control. In contrast, averaged 10 times more DAGs and DAMs were observed when performed comparison under different growing environments in three different ecological regions of China than the numbers induced by gene effects. Major biological pathways relating to stress response or signaling transduction could explain somehow the effects of growing environments. We further compared two transgenic events mediated ZD958 (GM-ZD958) with either transgenic parent GM-Z58, and other genetic background nonGM-Z58, nonGM-ZD958, and Chang7-2. We found that the numbers of DAGs and DAMs between GM-ZD958 and its one parent maize variety, Z58 or GM-Z58 is equivalent, but not Chang7-2. These findings suggest that greater effects due to different genetic background on altered molecular profiling than gene modification itself. This study provides a case evidence indicating marginal effects of gene pleiotropic effects, and environmental effects should be emphasized.